2022
DOI: 10.1098/rstb.2021.0345
|View full text |Cite
|
Sign up to set email alerts
|

Causal learning, counterfactual reasoning and pretend play: a cross-cultural comparison of Peruvian, mixed- and low-socioeconomic status U.S. children

Abstract: Pretend play universally emerges during early childhood and may support the development of causal inference and counterfactual reasoning. However, the amount of time spent pretending, the value that adults place on pretence and the scaffolding adults provide vary by both culture and socioeconomic status (SES). In middle class U.S. preschoolers, accuracy on a pretence-based causal reasoning task predicted performance on a similar causal counterfactual task. We explore the relationship between cultural environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…The researchers found that children were more successful at answering CFR questions in PP conditions and children's PP and CFR responses were significantly correlated even after controlling for age effects. A related study was repeated with 3-4-year-old children from low-income children in Peru and the USA with similar resultschildren provided more causally consistent answers in the PP condition (Wente et al, 2022). Earlier work by Dias and Harris (1990) reported that when conditional premises are presented in a make-believe mode either using a make-believe intonation, a fantastical setting like another planet, or through visual imagery, children will accept premises that violate their empirical knowledge as a basis for reasoning.…”
Section: Comparing the Cognitive Mechanisms Of Pretend Play And Count...mentioning
confidence: 78%
“…The researchers found that children were more successful at answering CFR questions in PP conditions and children's PP and CFR responses were significantly correlated even after controlling for age effects. A related study was repeated with 3-4-year-old children from low-income children in Peru and the USA with similar resultschildren provided more causally consistent answers in the PP condition (Wente et al, 2022). Earlier work by Dias and Harris (1990) reported that when conditional premises are presented in a make-believe mode either using a make-believe intonation, a fantastical setting like another planet, or through visual imagery, children will accept premises that violate their empirical knowledge as a basis for reasoning.…”
Section: Comparing the Cognitive Mechanisms Of Pretend Play And Count...mentioning
confidence: 78%
“…The researchers found that children were more successful at answering CFR questions in PP conditions and children's PP and CFR responses were significantly correlated even after controlling for age effects. A related study was repeated with 3–4‐year‐old children from low‐income children in Peru and the USA with similar results – children provided more causally consistent answers in the PP condition (Wente et al, 2022 ). Earlier work by Dias and Harris ( 1990 ) reported that when conditional premises are presented in a make‐believe mode either using a make‐believe intonation, a fantastical setting like another planet, or through visual imagery, children will accept premises that violate their empirical knowledge as a basis for reasoning.…”
Section: Introductionmentioning
confidence: 87%
“…The discrepancy between notions of single possibilities and modal possibilities is also a recurring point of contention in the developmental literature on counterfactual reasoning. One research tradition takes a broad definition of counterfactual reasoning, including any forms of thinking involving the generation of single alternatives to reality [59,60]-as in Wente et al's [54] study. Another research tradition, by contrast, includes only the specific form of thinking where one imagines what the present situation would be like had a past event turned out differently [61,62].…”
Section: (B) Early and Late Developments In Human Thinking About Poss...mentioning
confidence: 99%
“…Harris' [48] framework provides a useful lens for interpreting some of the new empirical data presented in this issue. In one contribution, Wente et al [54] examine the relationship between pretend play and reasoning about possibilities in 3-to 4-year-old children from Peru and the USA. The counterfactual task in this study required children to mentally simulate what would happen if one aspect of a previously shown causal scenario were altered, such that the children had to generate a single novel possibility to pass.…”
Section: (B) Early and Late Developments In Human Thinking About Poss...mentioning
confidence: 99%